2006
DOI: 10.1080/10715760600617843
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10: Absorption, tissue uptake, metabolism and pharmacokinetics

Abstract: Available data on the absorption, metabolism and pharmacokinetics of coenzyme Q10 (CoQ10) are reviewed in this paper. CoQ10 has a fundamental role in cellular bioenergetics. CoQ10 is also an important antioxidant. Because of its hydrophobicity and large molecular weight, absorption of dietary CoQ10 is slow and limited. In the case of dietary supplements, solubilized CoQ10 formulations show enhanced bioavailability. The T(max) is around 6 h, with an elimination half-life of about 33 h. The reference intervals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
325
1
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 464 publications
(348 citation statements)
references
References 59 publications
9
325
1
13
Order By: Relevance
“…Furthermore it is also a cofactor of mitochondrial uncoupling proteins, which activation leads to a reduction of mitochondrial-free radical generation [50,51]. In our study, beside a described low tissue uptake [26,27], we found a 40 times increase of CoQ10 level in the liver tissue.…”
Section: Page 16 Of 42supporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore it is also a cofactor of mitochondrial uncoupling proteins, which activation leads to a reduction of mitochondrial-free radical generation [50,51]. In our study, beside a described low tissue uptake [26,27], we found a 40 times increase of CoQ10 level in the liver tissue.…”
Section: Page 16 Of 42supporting
confidence: 53%
“…However, the effect of CoQ10 given orally remains only poorly explored in the context of obesity and diabetes. Among the tissues targeted through oral administration of CoQ10, the liver could be the most relevant since this tissue collects it with quite efficacy, and is thus considered as one of the storage pool of CoQ10 [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquinone (oxidized state) is reduced to ubiquinol (reduced state) either during or following absorption in the intestine and with about 95% of circulating CoQ10 exists in ubiquinol form (Bhagavan and Chopra, 2006). So their activity is not affected which form (reduced or oxidized) it is consumed.…”
Section: Coenzyme Q10 Absorption Among Body Tissuesmentioning
confidence: 99%
“…Due to its lipophilic nature and higher molecular weight (863 Da), the oral bioavailability of CoQ10 is low (Krizman et al, 2012). Following absorption, it is taken up by the liver for incorporation into Very Low Density Lipoprotein (VLDL) particles before released into circulation (Bhagavan and Chopra, 2006). Kaikkonen et al (1997) reported an elevated Q10 content in VLDL and Low Density Lipoprotein (LDL) fraction by 160% following dietary supply.…”
Section: Chemistry Of Coenzyme Q10mentioning
confidence: 99%
See 1 more Smart Citation